177k views
1 vote
Factor the expression.
x2 + 8x+ 16
x² + 3x+ 16 =

User Taymour
by
5.5k points

1 Answer

4 votes

Answer: 17x^2 + 11x + 16

Explanation:

The first term is, 17x^2 its coefficient is 17 .

The middle term is, +11x its coefficient is 11 .

The last term, "the constant", is +16

Step-1 : Multiply the coefficient of the first term by the constant 17 • 16 = 272

Step-2 : Find two factors of 272 whose sum equals the coefficient of the middle term, which is 11 .

-272 + -1 = -273

-136 + -2 = -138

-68 + -4 = -72

-34 + -8 = -42

-17 + -16 = -33

-16 + -17 = -33

User Aung Myat Hein
by
6.1k points